Optimisation of browning index of Maillard reaction in gelatine powder by response surface methodology (RSM) for halal authentication - Hamid, Anis Hamizah; Elgharbawy, Amal A.M.; Rohman, Abdul; Othman, Rashidi; A. Monsur, Hammed Ademola; Ahmad Fadzillah, Nurrulhidayah (Rynnye Lyan Resources, 2019)
Gelatine as the product of collagen extraction from animals is widely used in the food industry. In a glance, the physical properties of gelatine from several sources such as fish, bovine and porcine are similar. Therefore, distinguishing between the sources of gelatine is a tedious task. The differentiation of the gelatine from its sources requires an approach of a chemical reaction. This paper focused on the optimisation of Maillard reaction from different sources of gelatine by Response surface methodology (RSM). The experiment was designed with several imperative parameters; temperature, time and presence of metal ion Cu2+. The response was recorded from the absorbance of reacted gelatine mixture at specific wavenumber (420 nm) through UV-Vis instrumentation. The optimal reaction condition of all type of gelatines in water bath was 95°C for 9 hrs. From solution given, only 5mM concentration of metal ion Cu2+ has an influence on the bovine gelatine compared to fish and porcine gelatine. Maillard reaction with a combination of UV-Vis spectroscopy is one of the convenient protocols for rapid authentication purpose. RSM help to optimize the reaction condition of gelatine from different sources.